2020
DOI: 10.3389/fnins.2020.00129
|View full text |Cite
|
Sign up to set email alerts
|

Platelets in Amyloidogenic Mice Are Activated and Invade the Brain

Abstract: Alzheimer's disease (AD) is a neurodegenerative disease with a complex and not fully understood pathogenesis. Besides brain-intrinsic hallmarks such as abnormal deposition of harmful proteins, i.e., amyloid beta in plaques and hyperphosphorylated Tau in neurofibrillary tangles, blood-derived elements, in particular, platelets have been discussed to be involved in AD pathogenesis. The underlying mechanisms, however, are rather unexplored. Here, we investigate a potential role of platelets in an AD transgenic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…On the other hand, platelet activation as the critical process has been associated with brain aging and neurodegenerative pathogenesis. The platelet activation process might trigger brain vascular abnormalities such as microvascular integrity disruption in depression conditions to preserve vascular integrity [ 52 ]. In a recent study, Ge Zhang and colleagues illustrated a disposition to platelet hyperactivity and micro-thrombosis risk in intestinal tissue in inflammatory bowel diseases, especially Crohn’s [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, platelet activation as the critical process has been associated with brain aging and neurodegenerative pathogenesis. The platelet activation process might trigger brain vascular abnormalities such as microvascular integrity disruption in depression conditions to preserve vascular integrity [ 52 ]. In a recent study, Ge Zhang and colleagues illustrated a disposition to platelet hyperactivity and micro-thrombosis risk in intestinal tissue in inflammatory bowel diseases, especially Crohn’s [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Very recent studies indicate that platelets can contribute to BBB disruption (Kopeikina et al, 2020 ; Wu et al, 2021 ) and can transfer Aβ from blood vessels into CNS (Wu et al, 2021 ; Table 1 ). Moreover, it was demonstrated that activated platelets from APP/PS1 transgenic mice invade brain parenchyma and are closely associated with astrocytes (Kniewallner et al, 2020 ) that are enriched with major brain gangliosides in lipid rafts of astroglial limitations and efficiently activate platelets (Sotnikov et al, 2013 ). Platelets and their secreted factors could affect many cell types involved in the regulation of BBB integrity including endothelial cells, astroglia, and pericytes (Fang et al, 2011 ; Gonzales et al, 2020 ; Kniewallner et al, 2020 ).…”
Section: Alzheimer’s Diseasementioning
confidence: 99%
“…Platelets are also involved in neuroplasticity [14]. Importantly, activated platelets are capable of affecting the structural integrity of the BBB [29], penetrate and interact with the cellular components of the BBB matrix including astrocytes [30]. Relatedly, we found a positive correlation between plasma sP-selectin, and the astrocyte marker, S100B in patients with schizophrenia [17].…”
Section: Discussion/conclusionmentioning
confidence: 93%